Measurement of Transfort Properties for The Dried Layer of Several Food Materials Undergoing Freeze-Drying - Tetsuya Araki; A H Tambunan; K Abdullah (PERTETA, 1998)
The transport properties of several food materials have been presented as fundamental information to determine the drying rate of freeze-drying process. As an example, the measuring method of thermal conductyvity and permeability has been demonstrated for the sample of slices and mashed aplles undergoing freeze drying. Both samples were freeze - dried at constan surface temperatur ranging from -10 to 70 under the usual pressure range of commercial operation. A mathematical model, based on quasi-steady state analys, was formulated and then apllied to the drying data to determine these transport properties for the dried layer of the sample undergoing freeze drying. Values of thermal conductivity were found to be almost the same between sliced and mashed samples. However , the permeability data of mashed aplles were more than 4 timer greather than that sliced aplles.